2021
DOI: 10.1016/j.radi.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

3D virtual reality simulation in radiography education: The students' experience

Abstract: Introduction Simulation forms a key element of undergraduate Radiography education as it enables students to develop their clinical skills in a safe environment. In this study, an immersive three-dimensional (3D) virtual radiography simulation tool was piloted in an undergraduate Radiography curriculum and user feedback retrieved. Methods The 3D virtual simulation tool by Virtual Medical Coaching Ltd was introduced to first year radiography students (n = 105). This tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 23 publications
1
87
0
2
Order By: Relevance
“…16,17 Although the simulated learning is commonly reported as the replacement for some clinical placements and practical classes, the simulations in the physical MRS laboratories and use of immersive three-dimensional (3D) virtual reality (VR) simulation tools such as VR software by Virtual Medical Coaching Ltd (Christchurch, New Zealand) and VERT (Vertual Ltd., East Yorkshire, UK) may not be feasible during the lockdown. 5,9,13,29 The CBS programs such as Shaderware Virtual Radiography (Darlington, UK), MRI Simulator (The Institute for Advanced Clinical Imaging, Georgia, USA) and Netrad (administered by University of Sydney, Cumberland, Australia) which are more readily applicable to the home-based learning environment are more COVID-19 compliant. 5,24 However, with preparations in advance, it is feasible for the students to utilise some immersive 3D VR simulation tools at home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Although the simulated learning is commonly reported as the replacement for some clinical placements and practical classes, the simulations in the physical MRS laboratories and use of immersive three-dimensional (3D) virtual reality (VR) simulation tools such as VR software by Virtual Medical Coaching Ltd (Christchurch, New Zealand) and VERT (Vertual Ltd., East Yorkshire, UK) may not be feasible during the lockdown. 5,9,13,29 The CBS programs such as Shaderware Virtual Radiography (Darlington, UK), MRI Simulator (The Institute for Advanced Clinical Imaging, Georgia, USA) and Netrad (administered by University of Sydney, Cumberland, Australia) which are more readily applicable to the home-based learning environment are more COVID-19 compliant. 5,24 However, with preparations in advance, it is feasible for the students to utilise some immersive 3D VR simulation tools at home.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the VR software by Virtual Medical Coaching Ltd only requires generally available equipment such as HTC Vive Pro headsets and hand controllers (Taoyuan, Taiwan) for using it in the home-based learning environment. 29 With the high fidelity simulation tools, this might allow international MRS students to continue studying online for an extended period due to COVID-19 travel restrictions. 13,30 Nevertheless, findings of a survey study with 205 Australian academic, clinical and accrediting stakeholders published in 2011 shows that even for a well designed simulated learning program, it could only replace about 10e20% of clinical hours of a MRS course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tay et al [4] study in Singapore recognized the need for adaptation and suspension of clinical training for undergraduate students and the incorporation of simulation as part of the clinical model. Further, O'Connor et al [5] found that the use of 3D virtual radiography remained an invaluable pedagogical tool for student radiographers. In addition, its application for assessment purposes arguably provides an opportunity to explore an enhanced level of appropriateness of VR in future years.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, no other chiropractic institution or training program has implemented simulated radiography in their curriculum. Since completing this pilot study; however, literature has been published on the use of other virtual radiography software [ 10 , 11 ]. The Projection VR TM software has been well described by Shanahan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%